Factors That Affect Exercise Habits of College Students (Journal of Education and Development, 2018)
Various factors affect the exercise habits of college students. Some of these factors include sleep habits, diet, social life, homework, and other extracurricular activities. Although college students are aware of some of these influencing agents, they do not always take the necessary steps to change their habits. Exercise habits that an individual adheres to while in college would often determine their exercise habits for the rest of their lives. The purpose of this study was to determine the various factors that affect the exercise habits of college students. In this research, a convenience sample of 124 college students participated in a cross-sectional survey. The results indicated that the top reasons college students exercised was to remain healthy (M = 3.42, SD = 0.64), to gain the positive feeling that comes from exercise (M = 3.22, SD = 0.74); to join with friends who exercised (M = 2.99, SD = 0.72); and when feeling overweight (M = 2.96, SD = 0.88). Participants gave increased agreement to the item, “Having an increased homework load decreases the time I spend for exercise” (M = 3.10, SD = 0.86). This study may be useful for educators to teach and inform college students on the factors that affect exercise habits. A recommendation is to promote time management skills that are intentional about leaving adequate time for exercise. Teaching students how to balance personal life, school, and work will leave more time for them to exercise, and therefore, increase their health overall. Based on the health belief model, both positive and negative self-perceptions are motivating factors that causes people to take necessary steps to stay healthy.